Development of Local-Economic-Development Small and Medium Industries (Led-Sme) In East Java - Hidayat, Rachmad; Akhmad, Sabarudin (Makara Journal of Technology, 2012)
This paper presents the effects of Indonesian government’s developmental efforts of assistance and training performed on the growth of LED-SME business units and business performance. Both parameters of the government’s assistance and training were used to analyze the impact to the growth and performance of business unit. To achieve a comprehensive result, samples acquired in this research were about 190 entrepreneurs and managers of LED-SME from East Java. Based on the parameters above, there are five hypotheses made to prove the relationship of the assistance and training to the growth and performance of business units. The structural equation modeling (SEM) was carried out to test the hypotheses. The results have shown that the government’s developmental efforts through both assistance and training for the LED-SME were capable on increasing growth and performance of business units. On the other hand, government’s developmental efforts through only trainings were incapable of directly affecting growth of LED-SME business units and performance. To improve the business unit and performance, the government needs to implement developmental principles of LED-SME with the basis of utilizing local natural resources and also the communities of LED-SME as main suppliers for their local markets. In addition, preservation and development of local cultural and traditional arts also need to be the government’s main concern.